Levels of Health Theory With the Example of a Case of Juvenile Rheumatoid Arthritis - Dmitri Chabanov; Dionysis Tsintzas; George Vithoulkas (SAGE Publishing, 2018)
Objective. Contemporary medicine is in great need of a new patient health group classification that could be the basis for in-depth pathology assessments, disease development and prognosis, and the possibility of healing, as well as for possible complications of organism reactions to treatment processes. This classification is possible if founded on holistic approaches at the level of health assessment from the point of view of organism reactivity and resistance. Such a classification, assigning 12 levels and 4 health groups, exists in classical homeopathy. Methods. A new method for determining the group and level of health is shown in a case of juvenile rheumatoid arthritis of a generalized form in an 11-year-old girl, treated with classical homeopathy. The follow-up of the case is 18 years. Conclusion. The method allows the physician to assess the organism dynamics as a whole during the pathology development.